(untitled) (Hoboken, N.J., 2005)
This timely handbook provides practical information and evidence-based findings on the most effective and current prevention interventions and programmes available regarding adult emotional, mental health, and social problems. Each innovative chapter summarizes the problem, addressing trends, incidence, and risk factors; describes effective prevention interventions; and discusses practice and policy implications, as well as areas for future research. An exceptional resource for practitioners, researchers, and students alike, the Handbook of Preventive Interventions for Adults is an important addition to the mental health field.
Keywords: Medicine, Preventive,Preventive mental health services,Social service,Y học, Phòng bệnh,Dịch vụ phòng bệnh tâm thần,Dịch vụ xã hội